Beyond Ethylene: New Insights Regarding the Role of Alternative Oxidase in the Respiratory Climacteric - Hewitt, Seanna; Dhingra, Amit (Frontiers in Plant Science, 2020)
Climacteric fruits are characterized by a dramatic increase in autocatalytic ethylene production that is accompanied by a spike in respiration at the onset of ripening. The change in the mode of ethylene production from autoinhibitory to auto-stimulatory is known as the System 1 (S1) to System 2 (S2) transition. Existing physiological models explain the basic and overarching genetic, hormonal, and transcriptional regulatory mechanisms governing the S1 to S2 transition of climacteric fruit. However, the links between ethylene and respiration, the two main factors that characterize the respiratory climacteric, have not been examined in detail at the molecular level. Results of recent studies indicate that the AOX respiratory pathway may play an essential role in mediating cross-talk between ethylene response, carbon metabolism, ATP production, and ROS signaling during climacteric ripening. New genomic, metabolic, and epigenetic information sheds light on the interconnectedness of ripening metabolic pathways, necessitating an expansion of the current, ethylene-centric physiological models. Understanding points at which ripening responses can be manipulated may reveal key, species- and cultivar-specific targets for regulation of ripening, enabling superior strategies for reducing postharvest wastage.